Kerjasama Indonesia dan Amerika Serikat dalam Pelatihan Peacekeeper Melalui Garuda Canti Dharma II - Salsabila, Shafa; Sidik, Hasan (Indonesian Perspective, 2023)
Cooperation through the Garuda Canti Dharma exercise in 2022 is the second cooperation in the field of peacekeeping force training between Indonesia through the Indonesian Armed Forces Peacekeeping Centre and the United States through the United States Indo-Pacific Command (USINDOPACOM). Indonesia and the United States are countries that pay attention to peacekeeping operations. To solve the problem in the mission, a trained maintenance team is needed. Therefore, training through predeparture exercises and cooperation in training is needed in this regard. This article uses seven elements of international cooperation according to Messner, Guarín, and Haun in 2013 namely reciprocity, trust, communication, reputation, fairness, enforcement, and we-identity. By obtaining data through interviews and analysis from trusted journals and sources, the result is that each element of international cooperation is included in this cooperation.